2012
DOI: 10.1093/aob/mcs152
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of stress and mowing disturbance for the intensity and importance of plant interactions in dry calcareous grasslands

Abstract: At very high levels of stress, plant performances become too weak to allow either competition or facilitation and disturbance may accelerate the collapse of interactions in dry conditions. The results suggest that the importance and direction of interactions are more likely to be positively related in stressful environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 64 publications
8
50
0
2
Order By: Relevance
“…; Maalouf et al. ). Some studies have tried to minimize the problem of multiple independent environmental variables by focusing on systems where the dominant environmental gradients run approximately parallel (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Maalouf et al. ). Some studies have tried to minimize the problem of multiple independent environmental variables by focusing on systems where the dominant environmental gradients run approximately parallel (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…; Maalouf et al. ; Schöb et al. ), explicit consideration of several abiotic variables may offer improved understanding of the factors determining spatio‐temporal variation in the outcome of species interactions, particularly in habitats characterized by multiple key environmental variables.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the relationships between rainfall fluctuation and species interactions in arid regions will provide information that can be used to predict the responses of vegetation to future rainfall changes (Soliveres et al 2013). Many previous studies that have investigated the effects of water regimes on plant-plant interactions have often selected different locations along drought gradients (Armas et al 2011, Granda et al 2012, Kidron and Gutschick 2013, Ziffer-Berger et al 2014 or used varying water levels in controlled environments (Maalouf et al 2012, Gao et al 2014, Grant et al 2014, Rysavy et al 2014, Castanho et al 2015. However, few reports have addressed the balance between competition and facilitation along drought gradients from the same community for multiple growing seasons (but see Tielbörger and Kadmon 2000, Abdallah and Chaieb 2012, Metz and Tielbörger 2016, O'Brien et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…However, the few field studies that tested the predictions of the SGH for both intensity and importance show different patterns of variation along environmental gradients (e.g. Gaucherand et al 2006;McGeoch 2010, but see Armas et al 2011;Maalouf et al 2012).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Other studies have found that, at the stressful end of the gradient, the intensity of the positive net interaction reaches an asymptote (Kawai and Tokeshi 2007;le Roux and McGeoch 2010) or may wane and become neutral (Forey et al 2010;Maalouf et al 2012) or even negative (de Bello et al 2011;Koyama and Tsuyuzaki 2013). Some authors have proposed that the decrease in the net interaction most likely occurs because facilitators are less successful in ameliorating stress levels under very severe conditions, while competition for resources may decrease, remain constant or even increase with stress (Michalet et al 2006;Maestre et al 2009).…”
Section: Watering Treatmentmentioning
confidence: 99%